2018
DOI: 10.2139/ssrn.3226679
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Learner Autonomy and Autonomous Learning Practices in Massive Open Online Language Courses

Abstract: The study investigates the perception of learner autonomy with Massive Open Online Language Course (MOOLC) participants, more specifically; (i) to what extent EFL learners in an English MOOLC are autonomous, (ii) the perception of learners' and teachers' roles in learner autonomy, and (iii) the autonomous learning practices the learners are involved in by participating in the MOOLCs. It contributes to the understanding of online learner as an agent in highly heterogeneous language learning contexts and the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For the sake of this paper, learner autonomy is considered an individual and collective capacity that is fueled through a social interactive process. This is the process relied upon by the students and teachers of English as a Foreign Language for effective cooperation (Misir, Koc, & Koc, 2018). The concept of learner autonomy is therefore used as the foundational background within this literature review.…”
Section: Learner Autonomymentioning
confidence: 99%
“…For the sake of this paper, learner autonomy is considered an individual and collective capacity that is fueled through a social interactive process. This is the process relied upon by the students and teachers of English as a Foreign Language for effective cooperation (Misir, Koc, & Koc, 2018). The concept of learner autonomy is therefore used as the foundational background within this literature review.…”
Section: Learner Autonomymentioning
confidence: 99%
“…Other studies identify student autonomy as a defining feature of virtual learning [93,94]. Rice [95] found that students found remote learning challenging and alienating: "Even if students are highly driven and self-directed, they may still find the experience lonely, challenging, and disappointing in a distance education environment."…”
Section: 9mentioning
confidence: 99%
“…Language MOOCs, defined as "dedicated Web-based online courses for second languages with unrestricted access and potentially unlimited participation" (Bárcena and Martín-Monje, 2014), is an emergent and expanding field in foreign language education. Recent studies on LMOOCs from learners' perspective mainly focused on their motivation, learning experience and academic performance (Henry and Marrs, 2015;Charbonneau-Gowdy, 2016;Sallam et al, 2020), whereas learner autonomy and strategy choices have received scant attention (Mısır et al, 2018;Ding and Shen, 2019). Self-regulated learning (SRL), which has typically been studied in face-to-face learning environments, has received increasing attention in the context of MOOCs.…”
Section: Introductionmentioning
confidence: 99%